2005
DOI: 10.1016/j.febslet.2005.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Screening of genes expressed in developing mandibles during soldier differentiation in the termite Hodotermopsis sjostedti

Abstract: We investigated the morphological changes accompanying soldier differentiation in the damp-wood termite Hodotermopsis sjostedti. Genes expressed in the developing mandibles, which undergo the most remarkable morphological changes during soldier differentiation, were screened using fluorescent differential display. Database searches for sequence similarities were conducted and the relative expression levels were then quantified by real-time polymerase chain reaction. Among the identified candidate genes, 12 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 45 publications
(56 reference statements)
2
41
0
Order By: Relevance
“…Unfortunately, nearly 100 years of observational research through the 20th century yielded little information on the unique aspects of termite physiology and biochemistry that could be safely exploited for control purposes. Recent genomics-based research has begun to shift this paradigm (Miura et al, 1999;Scharf et al, 2003;Koshikawa et al, 2005;Hojo et al, 2005;Miura, 2005;Zhou et al, 2006a;Weil et al, 2007). Furthermore, recent functional genomics research has demonstrated that RNA interference (RNAi; Fire et al, 1998) is achievable in termites (Zhou et al, 2006b(Zhou et al, , c, 2007a, and that it can be used to address previously un-approachable research questions on termite sociality, nutrition, caste regulation, behavior, etc.…”
Section: Introductionmentioning
confidence: 95%
“…Unfortunately, nearly 100 years of observational research through the 20th century yielded little information on the unique aspects of termite physiology and biochemistry that could be safely exploited for control purposes. Recent genomics-based research has begun to shift this paradigm (Miura et al, 1999;Scharf et al, 2003;Koshikawa et al, 2005;Hojo et al, 2005;Miura, 2005;Zhou et al, 2006a;Weil et al, 2007). Furthermore, recent functional genomics research has demonstrated that RNA interference (RNAi; Fire et al, 1998) is achievable in termites (Zhou et al, 2006b(Zhou et al, , c, 2007a, and that it can be used to address previously un-approachable research questions on termite sociality, nutrition, caste regulation, behavior, etc.…”
Section: Introductionmentioning
confidence: 95%
“…Keywords Social insects 路 Caste differentiation 路 Gene expression 路 CYP15 路 JHAMT * Kiyoto Maekawa kmaekawa@sci.u-toyama.ac.jp 1 Graduate School of Science and Engineering, University of Toyama, 3190 Gofuku, Toyama 930-8555, Japan changes were identified (e.g., Cornette et al 2008bCornette et al , 2013Koshikawa et al 2005;Masuoka et al 2013;Toga et al 2012Toga et al , 2013Watanabe and Maekawa 2012). However, it is still unknown when the genes involved in JH biosynthesis are activated and/or the JH titer increases during soldier differentiation under natural conditions.…”
Section: Introductionmentioning
confidence: 98%
“…However, despite recent advances in the areas of termite endocrinology (Park and Raina, 2004;Mao et al, 2005) and gene-expression profiling (e.g. Miura et al, 1999;Scharf et al, 2003a;Scharf et al, 2005a;Miura, 2005;Koshikawa et al, 2005;Hojo et al, 2005;Cornette et al, 2006;Zhou et al, 2006c), our collective understanding of the molecular basis of termite caste regulation has remained limited. In this regard, the recent identification of the hexamerin caste-regulatory mechanism provided some of the first detailed molecular evidence of a casteregulating mechanism from a termite (Zhou et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%